Production constraints on cocoa agroforetry systems in West and Central Africa: the need for integrated pest management and multi-institutional approaches - Sonwa, D.J.; Weise, Stephan F.; Adesina, A.A.; Nkongmeneck, B.A.; Tchatat, M.; Ndoye, O. (2005)
Cocoa-producing countries of West and Central Africa experienced a serious economic crisis in the early 1980s, when the cocoa sector was liberalized and the macroeconomic policies of the sector changed. These institutional changes created new difficulties and challenges for sustainable cocoa farming. Farmers in this region have recently turned to timber and non-timber production to offset the fluctuation of cocoa prices. In a survey of 300 cocoa farmers in the humid forest zone of Southern Cameroon, pest and disease outbreaks were identified as the major limiting factors to sustainable cocoa production. An analysis of pests and diseases affecting the cocoa plantations in the humid forest zone of West and Central Africa revealed strong links to the type of forest cover found on or near the cocoa plantation. An integrated approach to pest management is proposed and the paper concludes with a discussion of current efforts to address constraints posed by pests and diseases on sustainable cocoa farming in the four main cocoa-producing countries of West and Central Africa.